2001
DOI: 10.1002/1526-4998(200101)57:1<3::aid-ps269>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Selecting the right compounds for screening: does Lipinski's Rule of 5 for pharmaceuticals apply to agrochemicals?

Abstract: Large numbers of compounds are now available through combinatorial chemistry and from compound vendors to screen for lead-level agrochemical activity. The likelihood that compounds with whole-organism activity will be discovered can be increased if compounds with physicochemical parameters consistent with transport to the target site are selected for screening. Certain ranges of simple parameters (molecular mass, log P, hydrogen-bond donors and acceptors, rotatable bonds) have been correlated with oral bioavai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
255
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(265 citation statements)
references
References 47 publications
6
255
0
4
Order By: Relevance
“…This is caused by the requirement to agrochemicals to resist to metabolic attack by the pest species. [30,40,41] Nevertheless, it can be stated that the conclusions reached in all these studies were very similar to each other and to the Lipinski's work. Leads are usually smaller and less lipophilic than launched active ingredients; MW and lipophilicity generally increase during the lead-to-drug optimization process.…”
Section: Similarity Of Drugs and Agrochemicalssupporting
confidence: 81%
“…This is caused by the requirement to agrochemicals to resist to metabolic attack by the pest species. [30,40,41] Nevertheless, it can be stated that the conclusions reached in all these studies were very similar to each other and to the Lipinski's work. Leads are usually smaller and less lipophilic than launched active ingredients; MW and lipophilicity generally increase during the lead-to-drug optimization process.…”
Section: Similarity Of Drugs and Agrochemicalssupporting
confidence: 81%
“…This nano-DEPA showed 8-fold lower median lethal concentration (48 h) for C. tritaeniorhynchus 3rd instar larvae (0.052 mg/dm 3 ) than bulk DEPA (0.416 mg/dm 3 ). Chitosan-coated nanoformulations of pyrifluquinazon were found to modify behaviour by rapid feeding cessation, so that insects (eg, green peach aphid, Myzus persicae) starve to death [177].…”
Section: Nanoinsecticidesmentioning
confidence: 84%
“…The antiparasitic activities of TiO 2 NPs synthesized by utilizing leaf aqueous extract of Catharanthus roseus against the adults of hematophagous fly, Hippobosca maculata Leach and sheep-biting louse, Bovicola ovis Schrank were evaluated by Velayutham et al [202]. The maximum activity of synthesized TiO 2 NPs was observed against H. maculata and B. ovis with LD 50 values of 7.09 and 6.56 mg/dm 3 , respectively, indicating that the use of TiO 2 NPs can be considered as an innovative alternative approach to control the hematophagous fly and sheep-biting louse. Moreover, Marimuthu et al [203] reported excellent anti-lousicidal activity of AgNPs against sheep body louse, B. ovis Schrank and human head louse, Pediculus humanus capitis De Geer.…”
Section: Nanoinsecticidesmentioning
confidence: 99%
See 2 more Smart Citations